2017
DOI: 10.25268/bimc.invemar.2017.46.1.708
|View full text |Cite
|
Sign up to set email alerts
|

Estructura De La Comunidad De Peces en La Bahía La Entrega, Oaxaca, México

Abstract: The ecological studieson the fish community in La Entrega Bay about its composition, diversity, distribution, and abundance7-288 Boletín de Investigaciones Marinas y Costeras • Vol. 46 (1) • 2017are insufficient, although it has one of the largest structured coral reef, with a variety of environments,habitats, and aquatic organisms poorly studied. Five samples were made in November 2002, March andApril 2003, which correspond to the dry season; and June and August 2003 during the rainy season,through visual cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
2
1
0
2
Order By: Relevance
“…With regard to the dominant families and species in our study, the findings are consistent with what has been reported for this locality (Juárez-Hernández et al 2013), adjacent bays (Ramírez-Gutiérrez et al 2007;López-Pérez et al 2010Ramos-Santiago and Tapia-García 2017;Tapia-García 2017, 2018a), and other regions on the Pacific coasts of Central Mexico (Chávez-Comparán et al 2010;Galván-Villa et al 2011 and Central America (Dominici-Arosemena and Wolff 2006, Benfield et al 2008, Myers et al 2011. Selar crumenophthalmus and Harengula thrissina were not considered to be dominant because of their limited temporal and spatial representation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…With regard to the dominant families and species in our study, the findings are consistent with what has been reported for this locality (Juárez-Hernández et al 2013), adjacent bays (Ramírez-Gutiérrez et al 2007;López-Pérez et al 2010Ramos-Santiago and Tapia-García 2017;Tapia-García 2017, 2018a), and other regions on the Pacific coasts of Central Mexico (Chávez-Comparán et al 2010;Galván-Villa et al 2011 and Central America (Dominici-Arosemena and Wolff 2006, Benfield et al 2008, Myers et al 2011. Selar crumenophthalmus and Harengula thrissina were not considered to be dominant because of their limited temporal and spatial representation.…”
Section: Discussionsupporting
confidence: 92%
“…En términos de la máxima riqueza y diversidad de especies, probablemente se debieron a las altas temperaturas y una gran producción derivada de los procesos costeros regionales que aumentaron la Ramírez-Gutiérrez et al (2007). The greater abundance in the dry season (January) and the larger number of species and diversity in the rainy season (July and September) are in concordance with other studies (Ramírez-Gutiérrez et al 2007, López-Pérez et al 2012, Juárez-Hernández et al 2013, Ramos-Santiago and Tapia-García 2017. Regarding maximum abundance, this was the result of an increase in the abundance of resident species (C. atrilobata and T. lucasanum) and the migration of species considered to be cyclic visitors (S. crumenophthalmus and Harengula thrissina) (López-Pérez et al 2012, Juárez-Hernández and, which was favored by the increased plankton production driven by the effect of the "Tehuano" winds that transport nutrient-rich water to the region (Monreal-Gómez and Salas de León 1998).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…López-Pérez et al (2010) indican que la especie identificada como P. viola es en realidad Pareques sp. A, ya que la primera únicamente se distribuye de Panamá a Perú (Allen y Robertson, 2008), sin embargo, P. viola se distribuye desde el golfo de California hasta Perú (Chao, 1995;Del Moral-Flores et al, 2013;Froese y Pauly, 2017), y se ha colectado en Michoacán (CPUM Colección de Peces) y Nayarit (EBMP-INP Colección Ictiológica), lo que se corresponde con la identificación de esta especie en el área de estudio (Ramos Santiago, 2004;Tapia García y Juárez Hernández, 2006;López-Pérez et al, 2008; Juárez-Hernández y Tapia-García, 2017), así como en otras localidades del Pacífico mexicano como el golfo de California, Nayarit, Colima, Jalisco y Michoacán (Moncayo-Estrada et al, 2006;Chávez-Comparan et al, 2010;López-Martínez et al, 2010;Galván-Villa et al, 2011;Calderón-Aguilera, 2012;González-Díaz y Soria-Barreto, 2013). En este sentido, también se ha señalado que la especie identificada como P. viola sea P. fuscovittatus, que presenta una distribución específica en el Pacífico central mexicano (Chao y Espinosa 2010; Froese y Pauly, 2017), aun cuando esta última es característica de profundidades superiores a 70 m (Robertson y Allen, 2006;Chao y Espinosa, 2010) por lo que su censo en los trabajos en la zona de estudio sería poco probable ya que en su mayoría los transectos se efectuaron a profundidades no superiores a 20 m.…”
Section: Discussionunclassified
“…Las especies censadas fueron identificadas de acuerdo con los trabajos de Allen y Robertson (1998) y Amezcua-Linares (2009), y para el arreglo taxonómico se consideró lo propuesto por Nelson (2006). Se realizó una consulta de los antecedentes específicos para el área de estudio que incluyó publicaciones (Ramírez-Gutiérrez et al, 2007;López-Pérez et al, 2008, 2010, 2012Juárez-Hernández et al, 2013), tesis (Juárez- Hernández, 2008;Ramírez-Gutiérrez, 2010;Ramos-Santiago, 2004), informes (Tapia-García y Juárez- Hernández, 2006) y consulta en línea de colecciones de peces mediante el Sistema Nacional de Información sobre Biodiversidad (SNIB) de la Comisión Nacional para el Conocimiento y Uso de la Biodiversidad (CONABIO) a fin de contrastar la presencia de las especies observadas. La distribución geográfica de las especies se verificó en las bases de datos Fishbase (Froese y Pauly, 2017) y Sistema de Peces del Pacífico Oriental (Robertson y Allen, 2008).…”
Section: Materials Y Métodosunclassified